Operative treatment of pancreatico-bronchial fistula - Thomson, BNJ (2004)
BACKGROUND: Pancreatico-bronchial fistulas are a rare complication of acute or chronic pancreatitis. Both conservative and surgical management have been described previously. CASE OUTLINE: The management of a 68-year-old woman with acute pancreatitis complicated by a pancreatico-bronchial fistula was reviewed. CT scanning and magnetic resonance cholangio-pancreatography demonstrated a pancreatic pseudocyst with extension into the posterior mediastinum and right pleura. Despite conservative management as well as ERCP with pancreatic stent insertion, the fistula failed to resolve. Successful management of this difficult problem was achieved with distal pancreatectomy and intercostal drainage. DISCUSSION: Pancreatico-bronchial fistulas may be managed conservatively, but there should be a low threshold for surgical intervention if endoscopic measures fail.